SISTEM PENGECEKAN PH AIR OTOMATIS MENGGUNAKAN SENSOR PH PROBE BERBASIS ARDUINO PADA SUMUR BOR - Hariyadi Hariyadi; Mahyessie Kamil; Putri Ananda (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2020)
One of water quality parameters is the degree of water. For most of people, water quality is considered important because it is not only about aesthetic. A good water for consumption to governmentissued regulation through Indonesian Minister of Health is has a pH 6.5 - 8.5 value ( Regulation of Minister of Healty No 907, 2002, about Term and Supervision of Water Quality Drinking, and Regulation of Minister of Healty No 416, 1990 about Term and Supervision of Water Quality). Although most of people in Bukittinggi still do not know whether the water from drill water used is worth consuming or not. Therefore, writer planned to build a device to measure the acidity (pH) of water to make it easier to identify the water to be used. Device made by author has same function as water pH device or pH meter that has been traded in general. This device uses a liquid acidity sensor circuit as a pH sensor. The processing of sensor result is carried out by sensors by using Arduino Uno, display the measurement results using LCD. This device is relatively accurate with the power supply using 9 V battery that available in the market so this device can be taken everywhere to make it easier to use when researching or field surveys.